Bio-based polyesters based on 2, 5-furandicarboxylic acid as 3D-printing materials: Design, preparation and performances. (May 2019) - Geng, Yiting; Wang, Zhao; Hu, Xiaoran; Li, Yan; Zhang, Qinan; Li, Yujie; Wang, Runguo; Zhang, Liqun
Graphical abstract: Highlights: The amorphous all-bio-based polyester material is synthesized with originally renewable monomers. Such polyester material could be applied in 3D printing technology, overcoming the environmental pollution and realising the sustainable development of 3D printing materials. The introduction of 2, 5-furandicarboxylic acid in the bio-polyester structure makes the bio-based polyester materials have excellent mechanical and thermal properties, and overcomes the defects of poor toughness and thermal stability of PLA. By changing the content of 1, 2-propanediol in raw material, a series of performance-adjustable polyester materials were prepared, The 3D printing of amorphous plastic was firstly studied by using the glass transition temperature to control the cooling and shaping of the material. Abstract: The 3D-printing technology allows to manufacture polymers into desired shape. This work presents novel bio-based copolyesters (PHPF) prepared by the polycondensation of 2, 5-furandicarboxylic acid, 1, 6-hexanediol and 1, 2-propanediol as 3D-printed materials. These PHPF exhibit superior thermal stability. By tailoring the contents of 1, 2-PDO, the PHPF exhibit optimum mechanical properties with tensile strength of 42.7 Mpa, elongation at break of 515% and impact strength of 35.62 KJ/m 2, respectively. The 3D-printed PHPF shows a satisfactory mechanical properties obtained from tensile test and reliable microstructure observed by SEM. Both the thermal stability and mechanical properties of PHPF were far beyond polylactide, a present most used bio-based 3D-printed polymer, which revealed PHPF deserve to be promising 3D-printing materials.